Major ion chemistry and suitability of groundwater resources for different utilizations in mica mining areas, Jharkhand, India - Soma Giri; Ashwani Kumar Tiwari; Mukesh Kumar Mahato; Abhay Kumar Singh (Geochemical Transactions)
Abstract Groundwater resources in mica mining areas of Jharkhand are vital for local communities, agriculture, and domestic utilization. The study investigates the major ion chemistry of groundwater in the mica mining regions, focusing on key physicochemical parameters such as pH, electrical conductivity (EC), total dissolved solids (TDS), and concentrations of major cations (Ca²⁺, Mg²⁺, Na⁺, K⁺) and anions (HCO₃⁻, Cl⁻, SO₄²⁻, NO₃⁻, F−). Groundwater samples from the study area were collected before the monsoon season, during the monsoon season, and after the monsoon season. The hydro-chemical analysis reveals that groundwater in the mica mining zones exhibits elevated levels of dissolved ions, with NO₃⁻, F−, Ca²⁺, Mg²⁺ and total hardness exceeding permissible limits set by Bureau of Indian Standards (BIS) for drinking purposes at some locations. Water Quality Index (WQI) assessments suggest that a significant proportion of groundwater samples fall into the “good” to “very good” category for drinking and about 29% of the samples fall under the “poor” category. The groundwater was generally suitable for irrigational use with exception of a few due to high salinity. The principal component analysis revealed rock weathering as a dominant source of ions along with anthropogenic sources like mining and agriculture contributing minorly to the ionic load. The predominant hydro-chemical facies identified were Ca-Mg-HCO3 and Ca-Mg-Cl-SO4 types. Both carbonate and silicate weathering play an important role in the geochemical signature of the groundwater in the area. The study implicates the potential health impacts of using the groundwater as drinking water without treatment at a few locations owing to high fluoride, nitrate and dissolved solids. The study also highlights the need for sustainable water management practices and regular monitoring of groundwater quality to mitigate the anthropogenic impacts on groundwater resources.